DOES EDUCATIONAL BACKGROUND INFLUENCE STUDENTS’ PUBLIC SPEAKING SKILL? REALITY VS STUDENTS’ PERSPECTIVE - Benni Ichsanda Rahman Hz; Achmad Ramadhan (Universitas Bengkulu, 2022)
The purposes of this study are to investigate the substantial difference in public speaking abilities between students with a natural science and social science background in their high school, and to investigate the students’ point of view related to this issue. This study is a case study approach that is naturally qualitative, which involved 163 students of English Education Study Program, at one state university on North Sumatera province. Semi-structured techniques were used for data collection. The data collected in this study then were inspected out by using two methods; statistical count for quantitative data related to students’ senior high school educational background, and particular substances analysis for qualitative data related to students’ performance in their public speaking. Questionnaire and interview were conducted to assemble the data related to students’ experiences and involvements in taking the public speaking subject and its practice based on their educational background in senior high school, and to collect the students’ opinion related to this difference. The analysis resulted that natural science students in average achieve score 3.58, meanwhile social science students in average achieve score 3.51. The difference is 0.07 point or 1.4%. The average score between the students in natural science and social science can be stated as not significantly different. In addition, generally, all the students who were interviewed believed that public speaking competency is not correlated with majoring in senior high school.